Relaxed hybrid routing to prevent consecutive attacks in mobile ad-hoc networks. Issue 2 (5th June 2023) - Gripsy, J. Viji; Kanchana, K.R.
In the current trends, Wi-Fi networks and cellular ad-hoc community (MANET) have yielded incredible opportunity and recognition. This opportunity and popularity insisted on many forms of studies to recognition on it. This enormously bendy nature of the MANET additionally creates many community performance associated and protection associated problems. Numerous security vulnerabilities threaten the technique in MANET in diverse ways. The new and changed protocol is called Secure Route Discovery-Ad-hoc On-demand Distance Vector (SRD-AODV) protocol. This protocol includes one-of-a-kind additives and techniques to offer each proactive and reactive answers through deploying powerful authentication the use of the Modified Elliptic Curve Diffie-Hellman Algorithm (MECDHA) techniques. This additionally aims to comfort the records packets and routing desk records and subsequently the incursion detection and prevention from sequential attacks in MANET.